(untitled) (Tazakka: Jurnal Pendidikan dan Keislaman, 2025)
The process of memorizing the Qur’an often faces challenges in maintaining long-term retention and a lack of structured evaluation, while research on the utrujah method in non-formal institutions remains limited. This study explores the planning, implementation, and obstacles of the utrujah method in improving Qur’an memorization at the Ibadurrahman Qur’an House, Payakumbuh. Using a qualitative case study approach, data were obtained through in-depth interviews with administrators, teachers, and students, direct observation, and documentation. Analysis involved data reduction, presentation, and conclusion drawing, with validity ensured through source and technique triangulation. Findings show systematic planning of the utrujah method, including teacher preparation, adaptive memorization targets, method adjustment to student abilities, and periodic progress records. This aligns with Islamic Religious Education theory emphasizing individual guidance to shape morals and spirituality, as outlined by Ibn Khaldun’s tarbiyah concept—gradual development according to a child’s nature. Implementation is structured with daily routines integrating spirituality and discipline, supported by personal teacher attention and external supervision, leading to significant memorization improvement. Challenges include varying student abilities, irregular attendance, difficulty with long/similar verses, and environmental distractions. These are addressed through personal guidance and parental collaboration. Overall, the utrujah method proves effective in enhancing Qur’an memorization through a personalized, adaptive, and integrated approach, with active teacher involvement in overcoming obstacles.